Diagnosis, management and treatment of hepatitis delta virus infection: Turkey 2017 Clinical Practice Guidelines - Yurdaydın, Cihan; Tabak, Fehmi; Kaymakoğlu, Sabahattin; Akarsu, Mesut; Akıncı, Esra G.; Akkız, Hikmet; Alkım, Canan; Çekin, Ayhan H.; Ö. Çuvalcı, Nefise; Demir, Kadir; Değertekin, Bülent; Dökmetaş, İlyas; et al. (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Yurdaydın C, Tabak F, Idilman R; Viral Hepatitis Guidelines Study Group. Diagnosis, management and treatment of hepatitis delta virus infection: Turkey 2017 Clinical Practice Guidelines. Turk J Gastroenterol 2017; 28(Suppl 2); S84-S89.